The mass transfer of chemical elements and of their compounds in agrocenoses - T. I. Borisochkina; A. D. Kotelnikova; O. B. Rogova (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
The analysis of publications on the mass transfer of chemical elements in agrocenosis in the soil – plant system was carried out. Methods for estimating the content of mobile forms of chemical compounds coming from the soil into plants are considered. The phenomena of antagonism and synergism are characterized, and the necessity to consider them while planning fertilizer application is indicated. It is shown that the phenomena of synergism and antagonism of elements can be used in agriculture to regulate the flow of heavy metals or radionuclides into agricultural products. A balance model for mass transfer of chemical elements in agrocenosis is analyzed. It is shown that the introduction of organic fertilizers in soil mostly leads to a positive balance of microelements in the agrosystem. To characterize the efficiency of fertilizer use an assessment of the balance of nutrients in the agrosystem is required. The removal of trace elements by agricultural crops increases with the use of mineral fertilizers in doses that are optimal for the cultivation of crops in the region. In some cases, the input of heavy metals with technogenic fallout may exceed the removal of metals by plants from the soil. It may cause the accumulation of metals in the system. In uncontaminated background areas, the levels of microelement intake from fertilizers and atmospheric fallout in agrocenoses are comparable.